All the little hopes eaudiobook - Weiss, Leah (Recorded Books, 2021)
A Southern story of friendship forged by books and bees, when the timeless troubles of growing up meet the murky shadows of World War II Deep in the tobacco land of North Carolina, nothing's been the same since the boys shipped off to war and worry took their place. Thirteen-year-old Lucy Brown is precocious and itching for adventure. Then Allie Bert Tucker wanders into town, an outcast with a puzzling past. Lucy figures the two of them can solve any curious crime they find—just like her hero, Nancy Drew. Their chance arises when a man goes missing and an eccentric gives them a mystery to solve that takes them beyond the ordinary. Then their quiet town, seasoned with honeybees and sweet tea, becomes home to a Nazi prisoner-of-war camp. More men go missing. And together, the girls embark on a journey to discover if we ever really know who the enemy is. Lush with Southern atmosphere, All the Little Hopes is the story of two girls coming of age as war creeps ever closer, blurring the difference between what's right, what's wrong, and what we know to be true. "Wrapped in hope and mystery, this beautifully crafted story, set under a warm North Carolina sun, is full of heart. You won't want to miss this one."—Kathleen Grissom, New York Times bestselling author of The Kitchen House and Glory Over Everything